2023
DOI: 10.1002/joc.8124
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Indian Ocean warming on rainfall of Sri Lanka

Pathmarasa Kajakokulan,
Gayan Pathirana,
Maheshi Dheerasinghe
et al.

Abstract: Recent studies have pointed out an increased warming over the tropical Indian Ocean (IO) and how such warming could alter the convection and rainfall in the region. In this study, using observational/reanalysis datasets from 1981 to 2020, we show that the early Maha rainfall of Sri Lanka (SL) has been increasing, and it is considerably influenced by the North‐western IO sea surface temperature (SST) increase in the second inter‐monsoon (SIM). A significant warming in the North‐western IO alters the zonal SST g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…S3). In addition, there are positive correlations in the western part, and negative correlations over the eastern Indian Ocean are accompanied by positive IOD patterns (Kajakokulan et al 2023a), which are stronger in the post-1980 period than in the pre-1980 period. Thus, in agreement with previous studies (e.g., Li et al 2016;Zhang et al 2022;Zhang and Mochizuki 2023), our results also exhibit the strongest positive IOD patterns since the 1980s then and have a strong relationship with precipitation over the wet zone of Sri Lanka.…”
Section: 2mentioning
confidence: 97%
See 2 more Smart Citations
“…S3). In addition, there are positive correlations in the western part, and negative correlations over the eastern Indian Ocean are accompanied by positive IOD patterns (Kajakokulan et al 2023a), which are stronger in the post-1980 period than in the pre-1980 period. Thus, in agreement with previous studies (e.g., Li et al 2016;Zhang et al 2022;Zhang and Mochizuki 2023), our results also exhibit the strongest positive IOD patterns since the 1980s then and have a strong relationship with precipitation over the wet zone of Sri Lanka.…”
Section: 2mentioning
confidence: 97%
“…For example, Kajakokulan et al (2023a) elucidated that the rainfall anomaly is observed to be higher at approximately 2.5 mm/day during the 2019 positive IOD event, in contrast to the 2016 negative IOD event, where a value of 3 mm/day is noted. Furthermore, the enhancement of wet conditions is robust over the wet zone of (Nisansala et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well recognized that the Asian monsoon is one of the strongest and most important monsoons in tropical climates, and it is known to have a significant impact on tropical countries (Tada et al, 2016). Sri Lanka (SL, between 5 55 0 -9 51 0 N and 79 42 0 -81 53 0 E), a tropical country located in the Indian Ocean (IO), is mainly influenced by the Asian monsoon (Jinadasa et al, 2020;Kajakokulan et al, 2023). As a result, SL's climate is subject to four seasons namely the North-East Monsoon (NEM or winter, December to February), South-West Monsoon (SWM or summer monsoon, May-September) as the primary seasons and First Inter-Monsoon (FIM, March-April) and Second Inter-Monsoon (SIM, October-November), as secondary seasons (Naveendrakumar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, NEM is drier and more stable compared to the summer monsoon (Rajeevan et al, 2012) and particularly effects the north-eastern part of the country. Moreover, the southwestern part of SL (wet zone) receives the highest rainfall during FIM, and SIM seasons (Kajakokulan et al, 2023;Thevakaran et al, 2019). Based on these seasonal fluctuations in rainfall and temperature, SL has been divided into four distinct spatial climatic zones namely the wet zone, dry zone, intermediate zone, and semiarid zone (Alahacoon & Edirisinghe, 2021).…”
Section: Introductionmentioning
confidence: 99%